Langkah dahsyat mencetak anak menjadi inovator Robbani / Abdullah Muhammad Abdul Mu'thi; penerjemah, Najib Junaidi; editor, Ainul Haris Umar T, Waznin Mahfuzh, J. Hariyadi - MU'THI, Abdullah Muhammad Abdul; Najib Junaidi; Ainul Haris Umar T; Waznin Mahfuzh; Hariyadi, J. (Sukses Publishing, 2015)
393 hlm. : ilus. ; 24 cm.